PELAKSANAAN LELANG EKSEKUSI PANITIA URUSAN PIUTANG NEGARA DITINJAU DARI ASPEK HUKUM ADMINISTRASI NEGARA - Gustina Rahayu; Suharizal Suharizal (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2019)
The Committee for State Debt Affairs (PUPN), which is in the center of the capital city of the State, is a committee to streamline the implementation of authority and duties. An institution called the State Receivables Affairs Agency was renamed the State Debt and Auction Agency which has now changed the Directorate General State Accounts Receivable and Auction which is then the Directorate General of State Assets, this Agency is directly under and is responsible to the Minister of Finance for operations in the city and regency areas. The Office of State Receivables and Auction Management is formed (hereinafter referred to as KPKNL) the name is the State Wealth and Auction Office (hereinafter referred to as KPKNL). Confiscated Auction of the State Receivables Affairs Committee is an auction carried out on confiscated goods of the State Receivables Affairs Committee which is a debt guarantee at state banks. if given by a government bank to a debtor when faced with a problem the debtor cannot repay his credit payment based on a agreed credit agreement, the bank has taken measures so that the debtor can pay off his credit payments, so in the case of non-performing loans as state accounts uncollectible. This research is a sociological juridical, namely the approach taken to applicable legal norms is related to the facts in the field. That since the issuance of the Decision of the Constitutional Court Number 77 / PUU-IX / 2011 concerning the testing of Law Number 49 Prp Year 1960 concerning the Committee on State Receivables with the State Constitution of the Republic of Indonesia in 1945 resulted in the decision that the Bank's State Owned Enterprise Receivables are not Other State Receivables so that the settlement of Receivables is no longer delegated to the Committee of State Receivables Affairs but the settlement of the Receivables can be settled through the mechanism of each banking company using the principles of a sound banking company. Based on the results of this study, suggestions are suggested. Further study in the State Financial Law relating directly to the State Debt Affairs Committee Execution concerning the delegation of authority previously carried out by the State Debt Affairs Committee under the Minister of Finance was then carried out through the mechanism of each banking company because this is directly related to the accountability of State finances.